Respuesta :
Answers:
14 + 18 ÷ 2 x 18 – 7 = 169
- 14 + 9 * 18 - 7
- 14 + 162 - 7
- 169
60 – 9 x 8 ÷ 8 x 6 = 6
- 60 - 72 / 8 * 6
- 60 + -216/4
- 60 - 54
- 6
15 x 10 + 12 ÷ 3 + 9 = 163
- 150 + 12 / 3 + 9
- 150 + 4 + 9
- 163
(10 ÷ 5)3 + 100 – 9 x 11 = 7
- 2 * 3 + 100 - 9 * 11
- 6 + 100 - 99
- 7
8 x 4 + 9 – 9 + 18 = 50
- 32 + 9 - 9 + 18
- 41 - 9 + 18
- 32 + 18
- 50
3 x 8 x 2 – 42 + 5 = 11
- 24 * 2 - 42 + 5
- 48 - 42 + 5
- 11
i hope this helps, good luck :)
Answer:
Step-by-step explanation:
14 + 18 ÷ 2 x 18 – 7 = 169
14 + 9 * 18 - 7
14 + 162 - 7
169
60 – 9 x 8 ÷ 8 x 6 = 6
60 - 72 / 8 * 6
60 + -216/4
60 - 54
6
15 x 10 + 12 ÷ 3 + 9 = 163
150 + 12 / 3 + 9
150 + 4 + 9
163
(10 ÷ 5)3 + 100 – 9 x 11 = 7
2 * 3 + 100 - 9 * 11
6 + 100 - 99
7
8 x 4 + 9 – 9 + 18 = 50
32 + 9 - 9 + 18
41 - 9 + 18
32 + 18
50
3 x 8 x 2 – 42 + 5 = 11
24 * 2 - 42 + 5
48 - 42 + 5
11